Clustering Based Energy Conservation Techniques for Wireless Sensor Network: A Survey - Wadhwa, Sakshi; kaur, Harpreet (International Journal of Computer Sciences and Engineering, 2015)
Life time of a sensor network is dependent on the power of the battery. In some applications scenarios, it is not possible to replace the dead batteries. Many researches are focusing on designing protocols and algorithms for wireless sensor networks to reduce the energy expenditure. Clustering is one of the best approaches to reduce the energy consumption. The Energy consumption is effected by the distance between sensors. In this Paper, we conducted a survey on the various approaches of clustering to study and design an energy efficient algorithm based on distance to make the clusters.